Beyond Dehydrocoupling: Group 2 Mediated Boron–Nitrogen Desilacoupling. Issue 50 (16th October 2015) - Liptrot, David J.; Arrowsmith, Merle; Colebatch, Annie L.; Hadlington, Terrance J.; Hill, Michael S.; Kociok‐Köhn, Gabriele; Mahon, Mary F.
Abstract: The alkaline‐earth element bis(trimethylsilyl)amides, [Ae{N(SiMe3 )2 }2 (thf)2 ] [Ae=Mg, Ca, Sr], are effective precatalysts for boron–nitrogen bond formation through the desilacoupling of amines, RR′NH (R=alkyl, aryl; R′=H, alkyl, aryl), and pinBSiMe2 Ph. This reactivity also yields a stoichiometric quantity of Me2 PhSiH and provides the first example of a catalytic main‐group element–element coupling that is not dependent on the concurrent elimination of H2 . Abstract : It 's a Si→N : Alkaline‐earth element (Ae) bis(trimethylsilyl)amides, [Ae{N(SiMe3 )2 }2 (thf)2 ] (Ae=Mg, Ca, Sr), are precatalysts for boron–nitrogen bond formation through the desilacoupling of amines, RR′NH (R=alkyl, aryl; R′=H, alkyl, aryl), and pinBSiMe2 Ph (pin=pinacolato; see scheme).